Study the Hydrophobicity/Oleophilicity Properties of Kapok Fibre and Its Performance in Diesel/Water Filtration - Abd Ghafar, Adam Danial; Rosniza Hussin (Progress in Engineering Application and Technology, 2022)
Kapok fibre is harvested from the seed of Ceiba pentandra. Kapok exhibit some unique characteristics that favors it to be the study subject for various researchers. Thus, study was conducted to find out the plausible of kapok fibre as a sorbent for diesel spill. The objectives of this study are to study the surface properties of kapok fibre and to evaluate the interaction mechanism of kapok fibre in diesel/water separation performance. Packing density of kapok fibre has been the parameter in this study and the determined packing densities to find the oil sorption capacity are 0.0506 gcm-3, 0.0759 gcm-3 and 0.1012 gcm-3. Packed kapok fibre was placed on the surface of diesel/water mixture for 30 minutes. The oil sorption capacity for packing densities of e 0.0506 gcm-3, 0.0759 gcm-3 and 0.1012 gcm-3 are 15.51 gg-1, 10.83 gg-1 and 8.75 gg-1 respectively. Diesel oil is successfully absorbed by kapok